2019
DOI: 10.1177/2059436419835771
|View full text |Cite
|
Sign up to set email alerts
|

How citizen journalists impact the agendas of traditional media and the government policymaking process in China

Abstract: “Citizen journalism” is a term used to refer to ordinary individuals who act as journalists during some part of the process of creating content for mainstream journalism coverage. In China, besides ordinary citizen journalists, some professional journalists have been regarded as citizen journalists if they write stories online that would otherwise not be publishable in traditional media. Unfortunately, since the real name registration system was launched on the Internet in 2012, the activities of both professi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 45 publications
1
6
0
1
Order By: Relevance
“…Since we are examining daily newspaper content, it is essential to consider the lagged effects or to control for the level of content 7 days before the present value (seven lags back). A 7-day time lag is also consistent with previous research examining the intermedia agenda-setting relationship between Twitter and (Conway et al, 2015;Conway-Silva et al, 2017Kushin, 2010;Luo & Harrison, 2019). A reported lag suggests that Instagram posts significantly predicted newspaper issue mentions 1-7 days before the issue mentions in the newspaper indices.…”
Section: Resultssupporting
confidence: 87%
“…Since we are examining daily newspaper content, it is essential to consider the lagged effects or to control for the level of content 7 days before the present value (seven lags back). A 7-day time lag is also consistent with previous research examining the intermedia agenda-setting relationship between Twitter and (Conway et al, 2015;Conway-Silva et al, 2017Kushin, 2010;Luo & Harrison, 2019). A reported lag suggests that Instagram posts significantly predicted newspaper issue mentions 1-7 days before the issue mentions in the newspaper indices.…”
Section: Resultssupporting
confidence: 87%
“…A study by Zeng et al (2019) on China demonstrates how messages shared by ordinary people on social media platform Weibo proved useful in contradicting and questioning the credibility of official Chinese media reports. Another study by Luo and Harrison (2019) concluded that interactions by citizens on Weibo were not only influencing policymaking, but also playing an agenda-setting role for traditional media.…”
Section: Introductionmentioning
confidence: 99%
“…Social media is an important channel for disseminating air quality information, promoting the environment protection actions (Hswen et al 2019). Public opinion on social media could affect traditional commercially oriented media, and the interaction between the public and policy agenda, that is, public participation has made journalism an ongoing process, ultimately affecting the content of traditional media and governments' behaviors (Luo and Harrison 2019). Public opinion online has become a competitive force in the process of agenda setting, which has a bidirectional impact on traditional agenda setting (Luo 2014).…”
Section: Theoretical Frameworkmentioning
confidence: 99%